Clinical Outcome between Ticagrelor versus Clopidogrel in Patients with Acute Coronary Syndrome and Diabetes - Peixun He; Xiaolin Luo; Jiabei Li; Yi Li; Xiaozeng Wang; Lan Huang; Jun Jin; Yaling Han (Cardiovascular Therapeutics)
Background. The increased thrombotic risk in patients with acute coronary syndrome (ACS) and diabetes highlights the need for adequate antithrombotic protection. We aimed to compare the 6-month clinical outcomes between ticagrelor and clopidogrel in patients with ACS and diabetes. Methods and Results. The study was a single-center, prospective, randomized, open-label, blinded endpoint, and controlled registry trial. A total of 270 ACS patients with diabetes were randomly assigned in a 1 : 1 ratio to either the ticagrelor group or the clopidogrel group. Follow-up was performed for 6 months, and the data on efficacy outcomes and bleeding events were collected. At 6 months, complete follow-up data were available for 266 (98.5%) of 270 patients, and 4 were lost to follow-up. There was no significant difference in the survival rate of the effective endpoints between the ticagrelor group (n=133) and the clopidogrel group (n=133) (HR 0.83, 95% CI 0.44–1.56, p=0.561), but the incidence of bleeding events in the ticagrelor group was higher than that in the clopidogrel group (HR 1.76, 95% CI 1.00–3.10, p=0.049). Conclusion. Ticagrelor did not improve the composite of nonfatal MI, target vessel revascularization, rehospitalization, stroke, and death from any cause; however, it significantly increased the incidence of bleeding events defined by the Bleeding Academic Research Consortium (BARC) criteria in Chinese patients with ACS and diabetes during the 6-month follow-up compared with clopidogrel.